Transforming Language Acquisition: A Comprehensive Study on the Synergistic Integration of Traditional and Digital Methodologies to Enhance Learner Engagement and Skill Development - Naif Alqurashi (European Scientific Journal, ESJ, 2025)
This study investigates the evolving paradigm of language acquisition, juxtaposing traditional learning methodologies with contemporary digital approaches. Utilizing a mixed-methods design, the research engaged a sample of 1,000 participants, including both language learners and educators, to gather comprehensive insights into their preferences and experiences. Data were collected through structured surveys and semi-structured interviews, allowing for an in-depth exploration of the perceived effectiveness of various instructional strategies.The findings reveal a marked preference for a blended learning approach that harnesses the strengths of both traditional and digital methods. Specifically, traditional methodologies are found to be more effective in developing speaking and listening skills, while digital platforms are preferred for vocabulary enhancement and reading comprehension. These results underscore the necessity for a holistic approach to language learning that integrates the benefits of face-to-face interaction, cultural immersion, and structured learning with the flexibility and accessibility afforded by digital technologies. Furthermore, the study highlights the importance of adaptability in language instruction, suggesting that educators should tailor their approaches to meet the diverse needs of learners in a rapidly changing educational landscape. Practical recommendations are provided for both learners and educators to optimize the language acquisition process in this digital age, including strategies for effectively integrating technology into traditional curricula and fostering meaningful human connections within the learning environment.